Non-aqueous electrolyte and lithium secondary battery comprising the same

CN122996531APending Publication Date: 2026-10-27LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202580023558.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-11-05
Filing Date
2025-11-06
Publication Date
2026-10-27

AI Technical Summary

Benefits of technology

[0030]本发明的非水电解质通过以特定组成比包含具有特定结构的两种腈化合物作为电解质添加剂,可以在负极表面上形成柔韧并且具有优异机械耐久性的固体电解质界面层。当本发明的非水电解质应用于锂二次电池时,该非水电解质可以吸收由于负极的连续体积膨胀和收缩造成的机械应力累积,并且可以抑制由负极表面上的固体电解质界面层的耐久性降低引起的电解质副反应加速、电阻增加和气体产生,从而大幅改善锂二次电池的寿命特性等整体性能。特别是,本发明的非水电解质可适用于包含在充放电过程中体积变化较大的硅类活性材料的负极以及包含该负极的锂二次电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to a non-aqueous electrolyte and a lithium secondary battery comprising the same. Specifically, the non-aqueous electrolyte of the present invention comprises a lithium salt, an organic solvent, and an additive, wherein the additive comprises a first additive and a second additive, the first additive is a compound represented by Chemical Formula 1, the second additive is a compound represented by Chemical Formula 2, the total content of the additive is 8 to 20 wt% based on the total weight of the non-aqueous electrolyte, and the weight ratio of the first additive to the second additive is 10:90 to 40:60.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-reference to related applications

[0002] This application claims priority to Korean Patent Application No. 10-2024-0164626, filed on November 18, 2024, and Korean Patent Application No. 10-2025-0165692, filed on November 5, 2025, the entire contents of which are incorporated herein by reference. Technical Field

[0003] This invention relates to a non-aqueous electrolyte and a lithium secondary battery containing the non-aqueous electrolyte. Background Technology

[0004] As modern society becomes increasingly reliant on electricity, the development of large-capacity energy storage devices capable of providing stable power and increasing output has attracted significant attention. Furthermore, with the performance improvements of electronic products ranging from small devices like mobile phones to medium and large electronic devices such as electric vehicles, the demand for high-capacity portable power supplies is growing. Lithium-ion batteries, with their highest potential, can meet the requirements for high-capacity energy storage performance and are therefore used in various applications, from small electronic devices to electric vehicles (EVs) and energy storage systems (ESS).

[0005] A lithium-ion secondary battery typically includes a positive electrode containing a positive active material, a negative electrode containing a negative active material, an electrolyte serving as the lithium-ion transport medium, and a separator. Lithium transition metal oxides such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium nickel cobalt manganese composite oxides, or lithium iron phosphate can be used as positive active materials, while carbon-based active materials, silicon-based active materials, lithium transition metal oxides, or lithium metal can be used as negative active materials.

[0006] When a lithium-ion battery is charged, lithium ions are generated from the positive electrode. These ions may accumulate or be alloyed and stored at the negative electrode, while the discharge process proceeds in the opposite direction. Here, most lithium ions are deposited / alloyed within the negative electrode active material, but some are reduced along with the organic and inorganic substances that constitute the electrolyte, forming a nanoscale organic-inorganic composite on the negative electrode surface. This organic-inorganic film is called the solid electrolyte interphase (SEI) layer. A solid electrolyte interphase can also be formed on the surface of the positive electrode active material through the oxidation reaction of the electrolyte-forming materials.

[0007] Traditionally, carbon-based active materials such as graphite have been primarily used as anode active materials. However, in recent years, the use of silicon-based active materials, which have higher capacity than carbon-based active materials, has been considered.

[0008] Silicon-based active materials have emerged as the next-generation anode material for lithium-ion batteries that require high energy density. This is not only due to their higher capacity compared to carbon-based active materials, but also because they are low-cost, non-toxic, environmentally friendly, and have a lower operating voltage.

[0009] However, silicon-based active materials suffer from lower initial efficiency compared to carbon-based anode materials due to their high initial irreversible capacity, leading to significant lithium depletion. In particular, silicon-based active materials experience substantial volume expansion and contraction due to crystal structure changes caused by lithium-ion insertion and extraction during charging and discharging. This large volume expansion and contraction reduces the durability of the solid electrolyte interface layer, significantly decreasing the conductivity of the anode and thus degrading its lifetime performance. This can induce a thick film formation reaction on the anode surface accompanied by continuous electrolyte decomposition, resulting in a severe increase in battery resistance and performance degradation.

[0010] Therefore, methods for forming a solid electrolyte interface layer with high elasticity, enhanced resilience, and stability that can withstand volume changes of silicon-based anodes during silicon-based battery operation have become an important research topic. Summary of the Invention

[0011] [Technical Issues]

[0012] The present invention aims to solve the above problems and provide a non-aqueous electrolyte that can form a flexible and mechanically durable solid electrolyte interface layer on the surface of the negative electrode.

[0013] Furthermore, the present invention aims to provide a lithium secondary battery with reduced gas generation and improved lifespan characteristics during high-temperature storage by including the aforementioned non-aqueous electrolyte.

[0014] [Technical Solution]

[0015] The present invention provides a non-aqueous electrolyte comprising a lithium salt, an organic solvent, and additives, wherein the additives include a first additive and a second additive, the first additive being a compound represented by the following chemical formula 1, and the second additive being a compound represented by the following chemical formula 2. Based on the total weight of the non-aqueous electrolyte, the total content of the additives is from 8% to 20% by weight, and the weight ratio of the first additive to the second additive is from 10:90 to 40:60.

[0016] [Chemical Formula 1]

[0017] N≡C-R1-F

[0018] In chemical formula 1, R1 can be an alkylene group having 1 to 5 carbon atoms. [Chemical Formula 2] N≡C-R2 In chemical formula 2, R2 can be an alkyl group having 2 to 10 carbon atoms.

[0019] [2] The present invention provides the non-aqueous electrolyte described in [1] above, wherein the organic solvent is a cyclic carbonate compound.

[0020] [3] The present invention provides the non-aqueous electrolyte described in [2] above, wherein the cyclic carbonate compound is at least one selected from ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentene carbonate, 2,3-pentene carbonate and vinylene carbonate.

[0021] [4] The present invention provides the non-aqueous electrolyte described in [2] or [3] above, wherein the cyclic carbonate compound is ethylene carbonate (EC).

[0022] [5] The present invention provides a non-aqueous electrolyte as described in at least one of [1] to [4] above, wherein the compound represented by chemical formula 1 is at least one selected from the compounds represented by chemical formulas 1A to 1C: [Chemical Formula 1A] N≡C-CH2F [Chemical Formula 1B] N≡C-CH2CH2F [Chemical Formula 1C] N≡C-CH2CH2CH2F.

[0023] [6] The present invention provides a non-aqueous electrolyte as described in at least one of [1] to [5] above, wherein the compound represented by chemical formula 2 is at least one selected from the compounds represented by chemical formulas 2A to 2C: [Chemical Formula 2A] N≡C-CH(CH3)2 [Chemical Formula 2B] N≡C-CH(CH2CH3)2 [Chemical formula 2C] N≡C-CH(CH3)CH2CH3.

[0024] [7] The present invention provides a non-aqueous electrolyte as described in at least one of [1] to [6] above, wherein the weight ratio of the first additive to the second additive is from 10:90 to 30:70.

[0025] [8] The present invention provides at least one of the non-aqueous electrolytes described in [1] to [7] above, wherein the total content of the additives is 10% to 20% by weight based on the total weight of the non-aqueous electrolyte.

[0026] [9] The present invention provides a non-aqueous electrolyte as described in at least one of [1] to [8] above, wherein the non-aqueous electrolyte further comprises at least one auxiliary additive selected from cyclic carbonate compounds, halogenated carbonate compounds, sulfonyl lactone compounds, sulfate compounds, phosphoric acid compounds, boric acid compounds, benzene compounds, amine compounds, silane compounds and lithium salt compounds.

[0027]

[10] The present invention provides a lithium secondary battery, which includes a positive electrode, a negative electrode opposite to the positive electrode, a separator disposed between the negative electrode and the positive electrode, and the non-aqueous electrolyte described above [1].

[0028]

[11] The present invention provides the lithium secondary battery described in

[10] above, wherein the negative electrode comprises a silicon-based active material.

[0029] [Beneficial Effects]

[0030] The non-aqueous electrolyte of the present invention, by including two nitrile compounds with specific structures as electrolyte additives in a specific composition ratio, can form a flexible solid electrolyte interface layer with excellent mechanical durability on the negative electrode surface. When the non-aqueous electrolyte of the present invention is applied to a lithium secondary battery, it can absorb the accumulation of mechanical stress caused by the continuous volume expansion and contraction of the negative electrode, and can suppress the accelerated electrolyte side reactions, increased resistance, and gas generation caused by the reduced durability of the solid electrolyte interface layer on the negative electrode surface, thereby significantly improving the overall performance of the lithium secondary battery, such as its lifespan characteristics. In particular, the non-aqueous electrolyte of the present invention is applicable to negative electrodes containing silicon-based active materials with large volume changes during charging and discharging, and to lithium secondary batteries containing such negative electrodes. Detailed Implementation

[0031] It will be understood that the terms or words used in this specification and claims are for illustrative purposes only and should not be construed as having the meanings defined in common dictionaries. Rather, they should be interpreted as having meanings and concepts consistent with the technical ideas of the invention, based on the principle that the inventors may appropriately define the concepts of the terms to best interpret the invention.

[0032] For example, it will be further understood that the terms “comprising,” “including,” or “having” in this specification specify the presence of the stated features, figures, steps, elements, or combinations thereof, but do not exclude the presence or inclusion of one or more other features, figures, steps, elements, or combinations thereof.

[0033] Furthermore, in the description of "a to b carbon atoms" in this specification, "a" and "b" each represent the number of carbon atoms contained in a specific functional group. That is, the functional group can contain "a" to "b" carbon atoms. For example, "alkylene with 1 to 5 carbon atoms" refers to an alkylene containing 1 to 5 carbon atoms, namely, -CH2-, -CH2CH2-, -CH2CH2CH2-, -CH2(CH3)CH-, -CH2CH2CH2CH2CH2-, and -CH(CH3)CH2CH2-.

[0034] Furthermore, in this specification, the term "alkylene" refers to a branched or unbranched aliphatic hydrocarbon group or functional group in the form of having a hydrogen atom removed from each of the carbon atoms at both ends of an aliphatic hydrocarbon group. In one embodiment, the alkylene group may be substituted or unsubstituted. Alkylenes include methylene, ethylene, propylene, isopropylene, butylene, isobutylene, tert-butylene, pentylene, and 3-pentylene, etc., and in other embodiments they may optionally have substituents.

[0035] Unless otherwise defined in the specification, the term "substitution" means that at least one hydrogen atom bonded to carbon is replaced by another element such as fluorine.

[0036] In addition, unless otherwise expressly stated, in this specification, "%" indicates weight.

[0037] The invention will be described in more detail below.

[0038] The non-aqueous electrolyte and lithium secondary battery of the present invention may include at least one of the following disclosed configurations, and may include any combination of technically possible configurations among the following configurations.

[0039] Non-aqueous electrolytes

[0040] This invention relates to non-aqueous electrolytes, and more specifically to non-aqueous electrolytes for lithium secondary batteries.

[0041] Specifically, the present invention provides a non-aqueous electrolyte comprising a lithium salt, an organic solvent, and additives.

[0042] The additive may include a first additive and a second additive.

[0043] The first additive can be a compound represented by the following chemical formula 1.

[0044] The second additive can be a compound represented by the following chemical formula 2.

[0045] Based on the total weight of the non-aqueous electrolyte, the total content of the additives can be from 8% to 20% by weight.

[0046] The weight ratio of the first additive to the second additive can be from 10:90 to 40:60.

[0047] [Chemical Formula 1]

[0048] N≡C-R1-F

[0049] In chemical formula 1, R1 can be an alkylene group having 1 to 5 carbon atoms.

[0050] [Chemical Formula 2]

[0051] N≡C-R2

[0052] In chemical formula 2, R2 can be an alkyl group having 2 to 10 carbon atoms.

[0053] The non-aqueous electrolyte of the present invention, by including a cyclic carbonate compound as an organic solvent and containing two nitrile compounds having specific structures in a specific composition ratio, can form a solid electrolyte interface layer with flexibility and excellent durability on the negative electrode surface. Therefore, when the non-aqueous electrolyte of the present invention is applied to a lithium secondary battery, a lithium secondary battery with improved lifespan and reduced gas generation during high-temperature storage can be provided.

[0054] (1) Lithium salts

[0055] As the lithium salt used in this invention, various lithium salts commonly used in non-aqueous electrolytes for lithium secondary batteries can be used without limitation. For example, the lithium salt may contain Li. + As a cation, and may contain F - Cl - ,Br - I - NO3 - N(CN)2 - BF4 - ClO4 - B 10 Cl 10 - AlCl4 - AlO2 - PF6 - CF3SO3 - CH3CO2 - CF3CO2 - AsF6 - SbF6 - CH3SO3 - (CF3CF2SO2)2N - (CF3SO2)2N - (FSO2)2N -BF2C2O4 - BC4O8 - PF4C2O4 - PF2C4O8 - (CF3)2PF4 - (CF3)3PF3 - (CF3)4PF2 - (CF3)5PF - (CF3)6P - C4F9SO3 - CF3CF2SO3 - CF3CF2(CF3)2CO - (CF3SO2)2CH - and CF3(CF2)7SO3 - At least one of them is used as an anion.

[0056] Specifically, lithium salts may include those selected from LiCl, LiBr, LiI, LiBF4, LiClO4, and LiB. 10 Cl 10 The lithium salt comprises one or a mixture of two or more of the following: LiAlCl4, LiAlO2, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiN(SO2F)2 (lithium bisfluorosulfonylimide, LiFSI), LiN(SO2CF2CF3)2 (lithium bisperfluoroethanesulfonylimide, LiBETI), and LiN(SO2CF3)2 (lithium bistrifluoromethanesulfonylimide, LiTFSI). Specifically, the lithium salt comprises at least one selected from the group consisting of LiBF4, LiClO4, LiPF6, LiBOB (LiB(C2O4)2), LiCF3SO3, LiTFSI (LiN(SO2CF3)2), LiFSI ((LiN(SO2F)2) and LiBETI (LiN(SO2CF2CF3)2).

[0057] The lithium salts mentioned above may vary appropriately within the generally available range, but may be included in the electrolyte at a concentration of 0.8M to 4.0M, specifically 1.0M to 3.0M, to achieve the best effect of forming a film that prevents corrosion of the electrode surface.

[0058] When the concentration of lithium salt is within the above range, the viscosity of the non-aqueous electrolyte can be controlled to achieve optimal impregnation and improve the mobility of lithium ions, thereby improving the capacity and cycle characteristics of lithium secondary batteries.

[0059] (2) Organic solvents

[0060] The non-aqueous electrolyte of the present invention may contain cyclic carbonate compounds as organic solvents.

[0061] Cyclic carbonate compounds can minimize decomposition due to oxidation reactions during charging and discharging, and are high-viscosity organic solvents that can readily dissociate lithium salts in non-aqueous electrolytes due to their high dielectric constant. Specific examples may include at least one organic solvent selected from ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentene carbonate, 2,3-pentene carbonate, and vinylene carbonate, among which ethylene carbonate may exhibit optimal lithium salt dissociation and film-forming effects.

[0062] On the other hand, even if the non-aqueous electrolyte of the present invention contains only cyclic carbonate compounds as organic solvents, it can readily dissolve non-aqueous electrolyte components such as lithium salts and the additives described below, and can achieve the appropriate mobility of lithium salts and the appropriate viscosity of non-aqueous electrolytes. Furthermore, preferably, the non-aqueous electrolyte of the present invention avoids the use of linear carbonate compounds containing carbonate functional groups, thereby suppressing the formation of byproducts that act as impedance at the negative electrode during reduction and reducing the generation of CO and CO2 gases during high-temperature storage.

[0063] On the other hand, unless otherwise stated, the non-aqueous electrolyte of the present invention, except for lithium salt, electrolyte additives and auxiliary additives described below, may be entirely composed of organic solvents.

[0064] (3) Additives

[0065] The non-aqueous electrolyte of the present invention may contain two nitrile compounds with different structures as additives.

[0066] Specifically, the additive may include a first additive and a second additive, wherein the first additive may be a compound represented by the following chemical formula 1, and the second additive may be a compound represented by the following chemical formula 2.

[0067] [Chemical Formula 1]

[0068] N≡C-R1-F

[0069] (In chemical formula 1, R1 is an alkylene group having 1 to 5 carbon atoms)

[0070] [Chemical Formula 2]

[0071] N≡C-R2

[0072] (In chemical formula 2, R2 can be an alkyl group having 2 to 10 carbon atoms).

[0073] Specifically, the nitrile compound represented by Formula 1 contains only one fluorine element at the end, thus exhibiting a small molecular size. Because this compound contains fluorine in its structure, it can form a solvated structure containing anion, and during charge-discharge, while decomposing on the negative electrode surface, it can form an inorganic solid electrolyte interface layer with high conductivity, flexibility, and excellent mechanical durability, such as lithium nitrogen / fluorine (LiF-Li3N). As a result, the degradation of the solid electrolyte interface layer caused by the continuous volume expansion and contraction of the negative electrode can be effectively suppressed, and the resistance can be reduced. When the compound represented by Formula 1 is substituted with more than two fluorine groups, for example, when the terminal group contains -CHF2 or -CF3 groups, or when at least one hydrogen in the alkylene group connecting the terminal nitrile group and the fluorine element is replaced by fluorine, the molecular size becomes bulky, and the desorption of fluorine is not smooth, thus degrading the effectiveness of LiF film formation.

[0074] Furthermore, compared to the compound represented by Formula 1, the compound represented by Formula 2 has a lower freezing point and viscosity, as well as a higher dielectric constant. Therefore, when the compound represented by Formula 1 and the compound represented by Formula 2 are used in combination as an electrolyte additive, this can reduce the electrolyte viscosity and improve ionic conductivity, thereby enhancing the impregnation properties, low-temperature performance, and fast-charging performance of the non-aqueous electrolyte. Therefore, when this non-aqueous electrolyte of the present invention is applied to lithium secondary batteries, it can improve output performance while exhibiting excellent lifetime performance and storage performance even under repeated charge-discharge conditions.

[0075] In particular, Li3N, as a film component formed from two nitrile compounds with different structures, ensures high lithium-ion mobility. Therefore, compared to anodes using graphite active materials, a film with high lithium-ion mobility can be formed on the surface of anodes using silicon-based active materials with lower conductivity, thereby improving ionic conductivity.

[0076] Furthermore, the compounds represented by Formula 1 or Formula 2 each contain a polar nitrile group (-CN) with a high dipole moment in their structure. This group forms ligands with transition metals, creating a stable CEI film on the positive electrode surface. This prevents side reactions between the positive electrode and the electrolyte during high-temperature storage and inhibits metal dissolution. Additionally, in the compounds represented by Formula 1 or Formula 2, the unshared electron pair of the nitrogen atom in the structure stabilizes the lithium salt anion, thereby suppressing HF generation caused by lithium salt decomposition, further improving the high-temperature storage characteristics of the secondary battery. Moreover, since the compounds represented by Formula 1 or Formula 2 do not contain functional groups capable of producing CO and CO2, the generation of CO and CO2 gases during high-temperature storage can be reduced.

[0077] Furthermore, in chemical formula 1, R1 is an alkylene group having 1 to 3 carbon atoms.

[0078] Specifically, the compound represented by Chemical Formula 1 may include at least one of the compounds represented by Chemical Formulas 1A to 1C: [Chemical Formula 1A] N≡C-CH2F [Chemical Formula 1B] N≡C-CH2CH2F [Chemical Formula 1C] N≡C-CH2CH2CH2F.

[0079] Furthermore, in chemical formula 2, R2 can be an alkyl group having 3 to 7 carbon atoms.

[0080] Specifically, the compound represented by chemical formula 2 may include at least one of the compounds represented by chemical formulas 2A to 2C: [Chemical Formula 2A] N≡C-CH(CH3)2 [Chemical Formula 2B] N≡C-CH(CH2CH3)2 [Chemical formula 2C] N≡C-CH(CH3)CH2CH3.

[0081] The additive of the present invention may include a first additive and a second additive, wherein the weight ratio of the first additive to the second additive may be 10:90 to 40:60, or 10:90 to 35:65, specifically 10:90 to 30:70.

[0082] When the composition ratio of the first additive to the second additive meets the above-mentioned range, the electrolyte viscosity and ionic conductivity can be appropriately adjusted, and a film of appropriate thickness can be formed that improves the durability of the positive and negative electrodes without increasing the cell resistance. As a result, the degradation of the solid electrolyte interface layer caused by the continuous volume expansion and contraction of the negative electrode during repeated charge and discharge can be effectively suppressed, thereby achieving excellent high-temperature durability and low-temperature output performance. For example, when the weight ratio of the second additive to the first additive is less than 60, the content of the first additive, which has high reducing power in the electrolyte solvation structure, is high. This promotes the formation of a fluorine-containing film by the first additive during charging. Since this increases the thickness of the fluorine-containing film, the film resistance increases excessively, which may degrade high-temperature durability. Furthermore, as the proportion of the second additive, which has a low freezing point, low viscosity, and high dielectric constant, decreases, the low-temperature physical properties of the electrolyte also deteriorate accordingly. This may degrade both high-temperature durability and low-temperature output characteristics. Furthermore, when the weight ratio of the second additive to the first additive exceeds 90, the content of the first additive in the electrolyte solvation structure decreases significantly, thus weakening the effect of the first additive in forming a fluorine-containing film, resulting in a film with poor mechanical durability. Consequently, the high-temperature durability of the battery may deteriorate.

[0083] Based on the total weight of the non-aqueous electrolyte, the total content of the additive can be 8% by weight or more, 9% by weight or more, or 10% by weight or more. Based on the total weight of the non-aqueous electrolyte, the total content of the additive can be 20% by weight or less, 19% by weight or less, 18% by weight or less, 17% by weight or less, 16% by weight or less, or 15% by weight or less. These numerical ranges can be combined without limitation. For example, based on the total weight of the non-aqueous electrolyte, the total content of the additive can be 8% to 20% by weight, 8% to 18% by weight, or 8% to 15% by weight. When the total content of the additive meets the above numerical ranges, a solid inorganic film can be uniformly formed on the surfaces of the positive and negative electrodes while minimizing the disadvantages such as side reactions, capacity reduction, and increased resistance caused by the additive, thereby effectively acting as an ion carrier and effectively suppressing side reactions between the electrolyte and the electrode. Moreover, it can effectively suppress the deterioration of the solid electrolyte interface layer caused by the continuous volume expansion and contraction of the negative electrode during repeated charge and discharge processes, thereby achieving excellent high-temperature durability and low-temperature output performance. On the other hand, when the total content of electrolyte additives in the non-aqueous electrolyte is less than 8% by weight, the physical properties of the electrolyte, such as ionic conductivity and viscosity, deteriorate, reducing the film formation caused by the electrolyte additives. This makes it impossible to effectively suppress the deterioration of the solid electrolyte interface layer caused by the continuous volume expansion and contraction of the negative electrode, and may lead to an increase in cell resistance. In addition, when the total content of electrolyte additives in the non-aqueous electrolyte exceeds 20% by weight, there is a disadvantage that the cell resistance increases during charging and discharging due to excessive formation of the solid electrolyte interface layer.

[0084] (3) Auxiliary additives

[0085] To prevent electrolyte decomposition under high-output conditions from causing negative electrode failure, or to further improve low-temperature high-rate discharge characteristics, high-temperature stability, overcharge protection, and battery expansion suppression at high temperatures, the non-aqueous electrolyte of this invention may, if necessary, also contain other auxiliary additives. When the non-aqueous electrolyte contains auxiliary additives, these auxiliary additives may be referred to as third additives.

[0086] The auxiliary additives may include at least one selected from cyclic carbonates, halogenated carbonates, sulcolepsy compounds, sulfates, phosphoric acids, borates, benzenes, amines, silanes, and lithium salts.

[0087] Cyclic carbonate compounds may include vinylene carbonate (VC) or vinyl ethylene carbonate. Based on the total weight of the non-aqueous electrolyte, the content of cyclic carbonate compounds can be from 1.0 wt% to 10 wt%, specifically from 1.0 wt% to 5.0 wt%. When the content of cyclic carbonate compounds meets the above range, it can effectively improve the battery's low-temperature output, high-temperature storage characteristics, and high-temperature lifespan characteristics while suppressing side reactions.

[0088] Halogenated carbonate compounds may include fluoroethylene carbonate (FEC).

[0089] The sulfonyl compounds may include at least one compound selected from 1,3-propanesulfonyl (PS), 1,4-butanesulfonyl, vinylsulfonyl, 1,3-propenesulfonyl (PRS), 1,4-butenesulfonyl, and 1-methyl-1,3-propenesulfonyl, preferably 1,3-propanesulfonyl (PS). The sulfonyl compounds form a stable SEI film on the negative electrode surface through a reduction reaction, thereby preventing side reactions between the negative electrode and the electrolyte at high temperatures and suppressing gas generation. Therefore, improved durability can be achieved during high-temperature storage. Based on the total weight of the non-aqueous electrolyte, the content of the sulfonyl compounds can be from 1.0 wt% to 10 wt%, specifically from 1.0 wt% to 5.0 wt%. When the content of the sulfonyl compounds meets the above range, a robust film can be formed on the surfaces of the positive and negative electrodes, thereby effectively preventing the degradation of the positive and negative electrodes during high-voltage charging and high-temperature storage.

[0090] Sulfate compounds may include ethylene sulfate (Esa), trimethylene sulfate (TMS), or methyltrimethylene sulfate (MTMS). Based on the total weight of the non-aqueous electrolyte, the content of sulfate compounds can range from 0.01 wt% to 10 wt%, specifically from 0.05 wt% to 5.0 wt%. When the content of sulfate compounds meets the above range, side reactions in the electrolyte during charge and discharge can be suppressed, and a robust SEI film can be formed, thereby achieving excellent results in improving lifetime characteristics.

[0091] The phosphoric acid compound may include one or more compounds selected from lithium difluorodioxarate phosphate, lithium difluorophosphate, tris(trimethylsilyl) phosphate, tris(2,2,2-trifluoroethyl) phosphate, and tris(trifluoroethyl) phosphate. Based on the total weight of the non-aqueous electrolyte, the content of the phosphoric acid compound may be from 0.01 wt% to 10 wt%, specifically from 0.05 wt% to 5.0 wt%. When the content of the phosphoric acid compound meets the above range, a robust SEI film is formed, thereby improving the battery's low-temperature output, high-temperature storage characteristics, and high-temperature lifespan.

[0092] Boric acid compounds may include tetraphenylborate, lithium difluorooxalate borate (LIODFB), or lithium dioxalate borate (LiB(C2O4)2; LiBOB), and preferably may include lithium difluorooxalate borate. Based on the total weight of the non-aqueous electrolyte, the content of boric acid compounds may be from 1.0 wt% to 10 wt%, specifically from 1.0 wt% to 5.0 wt%. When the content of boric acid compounds meets the above range, a robust film is formed on the surfaces of the positive and negative electrodes, while preventing side reactions in the electrolyte, thereby effectively preventing the degradation of the positive and negative electrodes during high-voltage charging and high-temperature storage.

[0093] The nitrile compounds may include at least one compound selected from succinic anionyl nitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valerate, octanoic anionyl nitrile, heptanonitrile, cyclopentaneformitrile, cyclohexaneformitrile, 2-fluorobenzyl nitrile, 4-fluorobenzyl nitrile, difluorobenzyl nitrile, trifluorobenzyl nitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile. Based on the total weight of the non-aqueous electrolyte, the content of the nitrile compounds may be from 1.0 wt% to 10 wt%, specifically from 1.0 wt% to 5.0 wt%. When the content of the nitrile compounds meets the above range, a robust film is formed on the surfaces of the positive and negative electrodes, thereby suppressing gas generation caused by side reactions between the positive electrode and the electrolyte, and effectively suppressing the dissolution of metallic foreign matter.

[0094] Benzene compounds may include fluorobenzene, and amine compounds may include triethanolamine or ethylenediamine, etc. Based on the total weight of the non-aqueous electrolyte, the content of benzene compounds may be from 0.01% by weight to 10% by weight, specifically from 0.05% by weight to 5.0% by weight.

[0095] Silane compounds may include tetravinylsilane. Based on the total weight of the non-aqueous electrolyte, the content of silane compounds may be from 0.01% by weight to 10% by weight, specifically from 0.05% by weight to 5.0% by weight.

[0096] Lithium salts are compounds that are different from lithium salts contained in electrolytes, and may include one or more compounds selected from the group consisting of LiPO2F2, LiODFB, LiBOB (lithium dioxolaneborate, LiB(C2O4)2) and LiBF4.

[0097] In the case of ethylene carbonate, vinyl ethylene carbonate, or succinate, which are among these auxiliary additives, a more robust SEI film can be formed on the negative electrode surface during the initial activation process of the secondary battery.

[0098] The auxiliary additives can be used as a mixture of two or more of these additives, and their content can be less than 30% by weight, specifically from 0.01% to 10.0% by weight, preferably from 0.05% to 5.0% by weight, based on the total weight of the electrolyte. If the content of the auxiliary additives is less than 0.01% by weight, the effect of improving low-temperature output, high-temperature storage characteristics, and high-temperature life characteristics is not significant. If the content of the auxiliary additives is greater than 30% by weight, there is a possibility that excessive side reactions may occur in the electrolyte during the charging and discharging of the battery. In particular, if the additives used to form the SEI film are added in excess, the additives may not decompose sufficiently at high temperatures, and thus may exist as unreacted substances at room temperature or may precipitate in the electrolyte. Therefore, side reactions that degrade the life or resistivity characteristics of the secondary battery may occur.

[0099] Lithium secondary batteries

[0100] Furthermore, in another embodiment of the present invention, the present invention provides a lithium secondary battery comprising a positive electrode, a negative electrode opposite to the positive electrode, a separator disposed between the negative electrode and the positive electrode, and the aforementioned non-aqueous electrolyte.

[0101] After forming an electrode assembly consisting of a positive electrode, a separator, and a negative electrode stacked sequentially and housing it in a battery casing, the lithium secondary battery of the present invention can be prepared by injecting the electrolyte of the present invention therein, and can be prepared and used according to conventional methods known in the art.

[0102] Since the non-aqueous electrolyte has already been explained above, the positive electrode, negative electrode, and membrane will be explained below.

[0103] (1) Positive electrode

[0104] The positive electrode of the present invention may contain a positive electrode active material.

[0105] The positive electrode active material is a compound capable of reversible insertion and extraction. It can be any positive electrode active material used in this field, without particular limitation, and may specifically include lithium metal composite oxides. More specifically, the lithium metal composite oxide may be: layered compounds such as lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), or compounds substituted with one or more transition metals; lithium iron oxides such as LiFe3O4; lithium iron phosphate such as LiFePO4; or lithium... 1+c1 Mn 2-c1 Lithium manganese oxides such as O4 (0≤c1≤0.33), LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxides (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, and Cu2V2O7; LiNi 1-c2 M c2 O2 (where M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B, and Ga, and satisfies 0.01 ≤ c2 ≤ 0.3) represents a Ni-site type lithium nickel oxide; LiMn 2-c3 M c3 Lithium manganese composite oxides such as O2 (where M is selected from at least one of the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1) or Li2Mn3MO8 (where M is selected from at least one of the group consisting of Fe, Co, Ni, Cu and Zn), but not limited to these.

[0106] Specifically, the lithium metal composite oxide may include at least one selected from lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese oxide, lithium-rich manganese oxide, and lithium iron phosphate.

[0107] More specifically, lithium nickel cobalt manganese oxide can be represented by the following chemical formula P-1.

[0108] [Chemical formula P-1]

[0109] Li 1+a Ni x Co y M 1 z M 2 w O2

[0110] In chemical formula P-1, M 1 Mn, Al, or a combination thereof M 2is at least one selected from Al, Zr, W, Ti, Mg, Ca and Sr, where 0≤a≤0.5, 0.55<x<1.0, 0<y≤0.4, 0<z≤0.4, 0≤w≤0.1. Here, x+y+z+w may be 1.

[0111] In Chemical Formula P-1, 1+a represents the molar ratio of lithium in the lithium nickel cobalt manganese composite oxide, which may satisfy 0≤a≤0.5, preferably 0≤a≤0.2, more preferably 0≤a≤0.1.

[0112] In Chemical Formula P-1, x represents the molar ratio of nickel in all transition metals other than lithium in the lithium nickel cobalt manganese composite oxide, which may satisfy 0.55<x<1.0, specifically 0.6≤x≤0.98, more specifically 0.7≤x≤0.98.

[0113] In Chemical Formula P-1, y represents the molar ratio of cobalt in all transition metals other than lithium in the lithium nickel cobalt manganese composite oxide, which may satisfy 0<y≤0.4, specifically 0<y≤0.3, more specifically 0.05≤y≤0.3.

[0114] In Chemical Formula P-1, z represents the molar ratio of element M in all transition metals other than lithium in the lithium nickel cobalt manganese composite oxide 1 , which may satisfy 0<z≤0.4, more preferably 0<z≤0.3, more preferably 0.01≤z≤0.3.

[0115] In Chemical Formula P-1, w represents the molar ratio of element M in all transition metals other than lithium in the lithium nickel cobalt manganese composite oxide 2 , which may satisfy 0<w≤0.1, preferably 0<w≤0.05, more preferably 0<w≤0.02.

[0116] The lithium nickel cobalt manganese oxide may be Li(Ni with a Ni content of 0.55 atomic% or more 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, Li(Ni 0.7 Mn 0.2 Co 0.1 )O2, Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, Li(Ni 0.86 Mn 0.07 Co 0.05 Al0.02 O2, Li(Ni) 0.90 Mn 0.05 Co 0.05 O2 or Li(Ni) 0.9 Mn 0.03 Co 0.06 Al 0.01 O2 is used to achieve high-capacity batteries.

[0117] On the other hand, the positive electrode active material can be in particulate form. Specifically, the average particle size (D) of the positive electrode active material... 50 The diameter can range from 1 μm to 30 μm.

[0118] The positive electrode may include a positive current collector and a layer of positive active material disposed on at least one surface of the positive current collector. Here, the positive active material may include the aforementioned positive active material.

[0119] As the positive current collector, various positive current collectors used in the art can be used. For example, stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, or silver can be used as the positive current collector.

[0120] The thickness of the positive electrode current collector can typically range from 3 μm to 500 μm, and fine irregularities can be formed on its surface to improve the adhesion of the positive electrode active material. Positive electrode current collectors can be used in various shapes, such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.

[0121] The positive electrode active material layer can be disposed on at least one surface of the positive electrode current collector. Specifically, the positive electrode active material layer can be disposed on one or both surfaces of the positive electrode current collector.

[0122] Considering the sufficient capacity of the positive electrode active material, the content of the positive electrode active material in the positive electrode active material layer can be from 70% to 99% by weight, preferably from 80% to 98% by weight.

[0123] The thickness of the positive electrode active material layer can be from 5 μm to 500 μm, preferably from 20 μm to 200 μm.

[0124] In addition, the positive electrode active material layer may also include conductive materials and / or adhesives together with the aforementioned positive electrode active material.

[0125] Conductive materials are used to impart conductivity to electrodes and can be used without any particular restrictions, as long as they do not cause chemical changes in the formed cell and possess electronic conductivity. Specific examples of conductive materials may include: carbon black, such as acetylene black (or Denka black), Ketjen black, channel black, furnace black, lamp black, or thermally cracked carbon black; graphite powder, such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers, such as carbon fibers or metal fibers; conductive powders, such as fluorocarbon powders, aluminum powder, or nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; polyphenylene derivatives, etc., and any one or a mixture of two or more of these may be used.

[0126] Based on the total weight of the positive electrode mixture layer, the content of conductive material can be from 0.1% to 10.0% by weight, preferably from 0.1% to 5.0% by weight.

[0127] Next, the adhesive can improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Examples of adhesives include any one or a mixture of two or more of the following: fluoropolymer adhesives including polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber adhesives including styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, or styrene-isoprene rubber; cellulose adhesives including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, or regenerated cellulose; polyol adhesives including polyvinyl alcohol; polyolefin adhesives including polyethylene or polypropylene; polyimide adhesives; polyester adhesives; and silane adhesives.

[0128] Based on the total weight of the cathode mixture layer, the binder content can be from 0.1% to 15.0% by weight, preferably from 0.1% to 10.0% by weight.

[0129] (2) Negative electrode

[0130] The present invention may include a negative electrode opposite to the positive electrode.

[0131] The negative electrode may contain a negative electrode active material.

[0132] The aforementioned anode active material may include silicon-based anode active materials.

[0133] Typical examples of silicon-based anode active materials may include those selected from metallic silicon (Si) and silicon oxide (SiO2). x The following are included: 0 ≤ x < 2; silicon carbide (SiC); and Si-Y alloys (where Y is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, or combinations thereof, and is not Si). Specifically, it may include elements selected from SiO2.x (0≤x<2) represents at least one of the compounds and silicon-carbon composites. When the silicon-based negative electrode active material is SiO2, since SiO2 does not react with lithium ions and therefore cannot store lithium, x is preferably within the above range. More preferably, the silicon-based active material can be SiO.

[0134] Element Y can be freely selected from the group consisting of Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db (dubnium), Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.

[0135] To ensure structural stability during charging and discharging and to reduce side reactions with the electrolyte, the average particle size (D) of silicon-based active materials is crucial. 50 The diameter can be from 1 μm to 30 μm, preferably from 2 μm to 15 μm.

[0136] In addition, if necessary, the negative electrode may also contain a carbon-based active material. The carbon-based active material may include at least one selected from graphite, hard carbon, soft carbon, carbon black, graphene, and fibrous carbon, and may preferably include graphite. For example, the graphite may be at least one of synthetic graphite and natural graphite.

[0137] To ensure structural stability during charging and discharging and to reduce side reactions with the electrolyte, the average particle size (D) of carbon-based active materials is crucial. 50 The diameter can be from 10 μm to 30 μm, preferably from 15 μm to 25 μm.

[0138] When the negative electrode contains a carbon-based active material along with the silicon-based negative electrode active material, the weight ratio of the silicon-based negative electrode active material to the carbon-based active material can be from 1:99 to 30:70, preferably from 3:97 to 15:85. When the mixing ratio of the silicon-based active material to the carbon-based active material meets the above range, excellent cycle performance can be ensured because the volume expansion of the silicon-based active material is suppressed while improving capacity characteristics.

[0139] The negative electrode may include a negative current collector and a layer of negative active material disposed on at least one surface of the negative current collector. Here, the negative active material may include the aforementioned negative active material.

[0140] As the negative current collector, commonly used negative current collectors in the art can be used, such as copper, stainless steel, aluminum, nickel, titanium, sintered carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, and aluminum-cadmium alloys. The thickness of the negative current collector can typically be from 3 μm to 500 μm, and similar to the positive current collector, fine irregularities can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. The negative current collector can be used in various shapes, such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics.

[0141] The negative electrode active material layer can be disposed on at least one surface of the negative electrode current collector. Specifically, the negative electrode active material layer can be disposed on one or both surfaces of the negative electrode current collector.

[0142] The thickness of the negative electrode active material layer can be from 5 μm to 500 μm, preferably from 5 μm to 100 μm.

[0143] To achieve sufficient capacity of the secondary battery while minimizing the impact of volume expansion / contraction on the battery, the content of the negative electrode active material in the negative electrode active material layer can be from 60% to 99% by weight.

[0144] The negative electrode active material layer may also include conductive materials and / or adhesives together with the aforementioned negative electrode active material.

[0145] Conductive materials are components used to further improve the conductivity of the negative electrode active material. The amount of conductive material added, based on the total weight of the negative electrode active material layer, can be less than 10% by weight, preferably less than 5% by weight, specifically from 0.1% to 5% by weight. Any conductive material can be used without particular limitation, as long as it is conductive and does not cause adverse chemical changes in the battery. Examples include: carbon black, such as acetylene black (or Denka black), Ketjen black, channel black, furnace black, lamp black, or thermally cracked carbon black; graphite powder, such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fibers, such as carbon fibers or metal fibers; conductive powders, such as fluorocarbon powder, aluminum powder, and nickel powder; conductive whiskers, such as zinc oxide whiskers and potassium titanate whiskers; conductive metal oxides, such as titanium oxide; or polyphenylene derivatives.

[0146] Adhesives are components that facilitate the bonding between conductive materials, active materials, and current collectors. Examples of adhesives may include: fluoropolymer adhesives, including polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber adhesives, including styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, or styrene-isoprene rubber; cellulose adhesives, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, or regenerated cellulose; polyol adhesives, including polyvinyl alcohol; polyolefin adhesives, including polyethylene or polypropylene; polyimide adhesives; polyester adhesives; and silane adhesives.

[0147] Based on the total weight of the negative electrode active material layer, the content of the binder can be from 0.1% to 15.0% by weight, preferably from 0.1% to 10.0% by weight.

[0148] (3) Diaphragm

[0149] The separator separates the negative and positive electrodes and provides a path for the movement of lithium ions. Any separator can be used without particular limitation, as long as it is generally used in secondary batteries. In particular, separators with excellent electrolyte retention and low resistance to lithium ion transport are preferred.

[0150] Specifically, porous polymer membranes can be used, such as those made from polyolefin polymers (e.g., ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, and ethylene / methacrylate copolymers), or laminated structures of two or more layers can be used. Alternatively, typical porous nonwoven fabrics can be used, such as nonwoven fabrics formed from high-melting-point glass fibers or polyethylene terephthalate fibers. Furthermore, coated diaphragms containing ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength, and diaphragms with single-layer or multi-layer structures can be selectively used.

[0151] The lithium secondary battery of the present invention, as described above, is suitable for use in portable devices such as mobile phones, laptops and digital cameras, as well as electric vehicles such as hybrid electric vehicles (HEVs).

[0152] The shape of the lithium secondary battery of the present invention is not particularly limited, but cylindrical, prismatic, pouch or buckle-shaped batteries made of cans can be used.

[0153] The lithium secondary battery of the present invention can be used not only as a battery cell for use as a power source for small devices, but also as a unit cell in medium and large battery modules that include multiple battery cells.

[0154] The invention will now be described in more detail with reference to embodiments. However, the invention may be embodied in many different forms and should not be construed as being limited to the embodiments set forth herein. Rather, these exemplary embodiments are provided to make this description sufficiently complete and to fully convey the scope of the invention to those skilled in the art.

[0155] Example

[0156] Example 1

[0157] (Preparation of non-aqueous electrolytes)

[0158] A non-aqueous electrolyte for lithium secondary batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, and then adding compounds represented by chemical formula 1A, chemical formula 2A, and ethylene carbonate (VC) as additives.

[0159] The contents of the compound represented by chemical formula 1A, the compound represented by chemical formula 2A, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium secondary batteries are 2 wt%, 6 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of chemical formula 1A to the compound of chemical formula 2A can be 25:75.

[0160] (Preparation of secondary batteries)

[0161] The positive electrode active material (Li(Ni) 0.8 Mn 0.1 Co 0.1 O2, conductive material (carbon black), and binder (polyvinylidene fluoride) were added to N-methyl-2-pyrrolidone (NMP) as a solvent in a weight ratio of 97.6:0.8:1.6 to prepare a positive electrode slurry (solids content: 60.0% by weight). A 13.5 μm thick positive current collector (Al film) was coated with the positive electrode slurry, dried, and rolled to prepare the positive electrode.

[0162] A negative electrode active material (Si), binder (SBR-CMC), and conductive material (carbon black) were added to water as a solvent in a weight ratio of 97.6:0.8:1.6 to prepare a negative electrode slurry (solid content: 60% by weight). A 6 μm thick negative electrode current collector (Cu film) was coated with the negative electrode slurry, dried, and rolled to prepare the negative electrode.

[0163] After preparing an electrode assembly by placing a porous polypropylene separator between the positive and negative electrodes, the electrode assembly is housed in a battery casing and injected with the non-aqueous electrolyte prepared above, thereby preparing a lithium secondary battery.

[0164] Example 2

[0165] (Preparation of non-aqueous electrolytes)

[0166] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) as additives. The contents of the compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium-ion batteries were 2.5 wt%, 7.5 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1A to the compound of Formula 2A could be 25:75.

[0167] (Preparation of secondary batteries)

[0168] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0169] Example 3

[0170] (Preparation of non-aqueous electrolytes)

[0171] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) as additives. The contents of the compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium-ion batteries were 3.75 wt%, 11.25 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1A to the compound of Formula 2A could be 25:75.

[0172] (Preparation of secondary batteries)

[0173] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0174] Example 4

[0175] (Preparation of non-aqueous electrolytes)

[0176] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) as additives. The contents of the compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium-ion batteries were 5 wt%, 15 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1A to the compound of Formula 2A could be 25:75.

[0177] (Preparation of secondary batteries)

[0178] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0179] Example 5

[0180] (Preparation of non-aqueous electrolytes)

[0181] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of compounds represented by Formula 1A, Formula 2B, and vinylene carbonate (VC) as additives. The contents of the compounds represented by Formula 1A, Formula 2B, and VC in the non-aqueous electrolyte for lithium-ion batteries were 2 wt%, 6 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1A to the compound of Formula 2B could be 25:75.

[0182] (Preparation of secondary batteries)

[0183] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0184] Example 6

[0185] (Preparation of non-aqueous electrolytes)

[0186] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of a compound represented by Formula 1A, a compound represented by Formula 2C, and vinylene carbonate (VC) as additives. The contents of the compound represented by Formula 1A, the compound represented by Formula 2C, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium-ion batteries were 2 wt%, 6 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1A to the compound of Formula 2C could be 25:75.

[0187] (Preparation of secondary batteries)

[0188] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0189] Example 7

[0190] (Preparation of non-aqueous electrolytes)

[0191] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of compounds represented by Formula 1B, Formula 2A, and vinylene carbonate (VC) as additives. The contents of the compounds represented by Formula 1B, Formula 2A, and VC in the non-aqueous electrolyte for lithium-ion batteries were 2 wt%, 6 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1B to the compound of Formula 2A could be 25:75.

[0192] (Preparation of secondary batteries)

[0193] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0194] Example 8

[0195] (Preparation of non-aqueous electrolytes)

[0196] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of a compound represented by Formula 1C, a compound represented by Formula 2A, and vinylene carbonate (VC) as additives. The contents of the compound represented by Formula 1C, the compound represented by Formula 2A, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium-ion batteries were 2 wt%, 6 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1C to the compound of Formula 2A could be 25:75.

[0197] (Preparation of secondary batteries)

[0198] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0199] Example 9

[0200] (Preparation of non-aqueous electrolytes)

[0201] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of compounds represented by Formula 1B, Formula 2B, and vinylene carbonate (VC) as additives. The contents of the compounds represented by Formula 1B, Formula 2B, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium-ion batteries were 2 wt%, 6 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1B to the compound of Formula 2B could be 25:75.

[0202] (Preparation of secondary batteries)

[0203] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0204] Example 10

[0205] (Preparation of non-aqueous electrolytes)

[0206] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) as additives. The contents of the compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium-ion batteries were 0.8 wt%, 7.2 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1A to the compound of Formula 2A could be 10:90.

[0207] (Preparation of secondary batteries)

[0208] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0209] Example 11

[0210] (Preparation of non-aqueous electrolytes)

[0211] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) as additives. The contents of the compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium-ion batteries were 3.2 wt%, 4.8 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1A to the compound of Formula 2A could be 40:60.

[0212] (Preparation of secondary batteries)

[0213] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0214] Comparative Example 1

[0215] (Preparation of non-aqueous electrolytes)

[0216] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) as additives. The contents of the compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium-ion batteries were 4 wt%, A wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1A to the compound of Formula 2A could be 50:50.

[0217] (Preparation of secondary batteries)

[0218] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0219] Comparative Example 2

[0220] (Preparation of non-aqueous electrolytes)

[0221] A non-aqueous electrolyte for lithium secondary batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M and then adding vinylene carbonate (VC) as an additive. The content of vinylene carbonate (VC) in the non-aqueous electrolyte for lithium secondary batteries was 0.5% by weight.

[0222] (Preparation of secondary batteries)

[0223] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0224] Comparative Example 3

[0225] (Preparation of non-aqueous electrolytes)

[0226] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) as additives. The contents of the compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium-ion batteries were 1.5 wt%, 4.5 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1A to the compound of Formula 2A could be 25:75.

[0227] (Preparation of secondary batteries)

[0228] A lithium secondary battery was prepared in the same manner as Comparative Example 1, except that the non-aqueous electrolyte prepared above was injected.

[0229] Comparative Example 4

[0230] (Preparation of non-aqueous electrolytes)

[0231] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) as additives. The contents of the compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium-ion batteries were 5.5 wt%, 16.5 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1A to the compound of Formula 2A could be 25:75.

[0232] (Preparation of secondary batteries)

[0233] In addition to injecting the non-aqueous electrolyte prepared above, a lithium secondary battery was prepared in the same manner as in Comparative Example 2.

[0234] Comparative Example 5

[0235] (Preparation of non-aqueous electrolytes)

[0236] A non-aqueous electrolyte for lithium secondary batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of a compound represented by Formula 1A and vinylene carbonate (VC) as additives. The contents of the compound represented by Formula 1A and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium secondary batteries were 8% by weight and 0.5% by weight, respectively.

[0237] (Preparation of secondary batteries)

[0238] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0239] Comparative Example 6

[0240] (Preparation of non-aqueous electrolytes)

[0241] A non-aqueous electrolyte for lithium secondary batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of a compound represented by Formula 2A and vinylene carbonate (VC) as additives. The contents of the compound represented by Formula 2A and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium secondary batteries were 8% by weight and 0.5% by weight, respectively.

[0242] (Preparation of secondary batteries)

[0243] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0244] Comparative Example 7

[0245] (Preparation of non-aqueous electrolytes)

[0246] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of difluoroacetonitrile, a compound represented by chemical formula 2A, and vinylene carbonate (VC) as additives. The contents of difluoroacetonitrile, the compound represented by chemical formula 2A, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium-ion batteries were 2 wt%, 6 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of difluoroacetonitrile to the compound of chemical formula 2A could be 25:75.

[0247] (Preparation of secondary batteries)

[0248] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0249] Comparative Example 8

[0250] (Preparation of non-aqueous electrolytes)

[0251] A non-aqueous electrolyte for lithium-ion batteries was prepared by dissolving LiPF6 in ethylene carbonate (EC) to 1.0 M, followed by the addition of compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) as additives. The contents of the compounds represented by Formula 1A, Formula 2A, and vinylene carbonate (VC) in the non-aqueous electrolyte for lithium-ion batteries were 0.56 wt%, 7.44 wt%, and 0.5 wt%, respectively. Furthermore, the weight ratio of the compound of Formula 1A to the compound of Formula 2A could be 7:93.

[0252] (Preparation of secondary batteries)

[0253] In addition to injecting the non-aqueous electrolyte prepared above, the lithium secondary battery was prepared in the same manner as in Example 1.

[0254] Experimental Example

[0255] Experimental Example 1. Evaluation of High-Temperature Storage Characteristics

[0256] After the lithium secondary batteries prepared in the examples and comparative examples were activated (formed) at a rate of 0.1 C for 3 hours, they were charged at 0.33 C at 25°C under CC / CV conditions to 4.2 V (0.05 C cutoff) to achieve a full charge of 100% SOC, and then stored at high temperature (60°C) for 8 weeks. Subsequently, the resistance was measured by transferring them to a charge / discharger at room temperature (25°C), and the rate of increase in resistance was calculated using the following mathematical formula 1, as shown in Table 1 below.

[0257] [Mathematical Expression 1]

[0258] Resistance increase rate (%) = {(resistance after high-temperature storage - initial resistance) / initial resistance} × 100

[0259] Experimental Example 2. Evaluation of High-Temperature Cycling Characteristics

[0260] After the lithium secondary batteries prepared in the examples and comparative examples were each activated (formed) at a rate of 0.1 C for 3 hours, they were charged at 25°C under CC / CV conditions at a rate of 0.33 C to 4.2 V (0.05 C cutoff) to achieve a full charge of 100% SOC. One cycle was defined as charging the fully charged battery at a high temperature (45°C) under CC / CV conditions at a rate of 0.33 C to 4.2 V and discharging it under CC conditions at a rate of 0.33 C to 2.8 V. 300 cycles were performed. Furthermore, the capacity retention rate after 300 cycles was calculated using the following mathematical formula 2, and the results are shown in Table 2 below.

[0261] [Mathematical Expression 2]

[0262] Capacity retention (%) = (Capacity after 300 cycles / Capacity after 1 cycle) × 100

[0263] Experimental Example 3. Evaluation of High-Temperature Preservation Characteristics

[0264] After the lithium secondary batteries prepared in the examples and comparative examples were activated (formed) at a rate of 0.1 C for 3 hours, they were charged at 25°C under CC / CV conditions at a rate of 0.33 C to 4.2 V (0.05 C cutoff) to achieve a full charge of 100% SOC. The volume of the secondary battery was measured and set as the initial volume of the secondary battery.

[0265] Subsequently, the fully charged batteries were stored at a high temperature (60°C) for 8 weeks, and the volume of the stored secondary batteries was measured again to calculate the increase in volume during the 8-week storage period.

[0266] The ratio of the increased volume to the initial secondary battery volume was calculated using the following mathematical formula 3, thus obtaining the volume increase rate after 8 weeks. The results are shown in Table 1 below.

[0267] [Mathematical Expression 3]

[0268] Volume increase rate (%) = {(Volume after 8 weeks of high-temperature storage - Initial volume) / Initial volume} × 100

[0269] Table 1

[0270] As can be seen from Table 1 above, compared with the lithium secondary batteries of Comparative Examples 1 to 8, the secondary batteries of Examples 1 to 11 of the present invention have improved resistance increase rate (%) after high-temperature storage and improved capacity retention rate (%) after high-temperature cycling.

[0271] Experimental Example 4. Evaluation of High-Rate Discharge Output

[0272] After the lithium secondary batteries prepared in the examples and comparative examples were activated (formed) at a rate of 0.1 C for 2 hours, they were charged at 0.33 C at 25°C under CC / CV conditions to 4.2 V (0.05 C cutoff) to achieve a full charge of 100% SOC. Then, the batteries were discharged at a rate of 0.2 C under constant current conditions to 2.8 V, and the discharge capacity was measured and set as the initial discharge capacity.

[0273] Subsequently, the secondary batteries were fully charged to 100% SOC at 0.33 C rate at 25°C. Each fully charged secondary battery was then discharged to 2.0 C rate under constant current conditions. The discharge capacity was measured and set as the high-rate discharge capacity.

[0274] The ratio of high-rate discharge capacity to initial discharge capacity is calculated using the following mathematical formula 4, and the high-rate discharge output is obtained. The results are shown in Table 2 below.

[0275] [Mathematical Expression 4]

[0276] High-rate discharge output (%) = (High-rate discharge capacity / Initial discharge capacity) × 100

[0277] Table 2

[0278] As can be seen from Table 2, the secondary batteries of Examples 1 to 11 of the present invention have improved high-rate discharge output (%) compared with the lithium secondary batteries of Comparative Examples 1 to 8.

[0279] Although the present invention has been described above with reference to embodiments thereof, those skilled in the art or with common knowledge in the field will understand that various modifications and changes to details can be made to the present invention without departing from the spirit and scope of the invention as set forth in the claims. Therefore, the scope of the present invention should be defined by the claims, and not by the description of the exemplary embodiments provided herein.

Claims

1. A non-aqueous electrolyte comprising a lithium salt, an organic solvent, and additives. in, The additives include a first additive and a second additive. The first additive is a compound represented by chemical formula 1. The second additive is a compound represented by chemical formula 2. Based on the total weight of the non-aqueous electrolyte, the total content of the additive is 8% to 20% by weight, and The weight ratio of the first additive to the second additive is 10:90 to 40:

60. [Chemical Formula 1] N≡C-R1-F In chemical formula 1, R1 is an alkylene group having 1 to 5 carbon atoms. [Chemical Formula 2] N≡C-R2 In chemical formula 2, R2 is an alkyl group having 2 to 10 carbon atoms.

2. The non-aqueous electrolyte as described in claim 1, wherein, The organic solvent is a cyclic carbonate compound.

3. The non-aqueous electrolyte as described in claim 2, wherein, The cyclic carbonate compound is selected from at least one of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentene carbonate, 2,3-pentene carbonate, and vinylene carbonate.

4. The non-aqueous electrolyte as described in claim 3, wherein, The cyclic carbonate compound is ethylene carbonate (EC).

5. The non-aqueous electrolyte as described in claim 1, wherein, The compound represented by chemical formula 1 is at least one selected from compounds represented by chemical formulas 1A to 1C: [Chemical Formula 1A] N≡C-CH2F [Chemical Formula 1B] N≡C-CH2CH2F [Chemical Formula 1C] N≡C-CH2CH2CH2F.

6. The non-aqueous electrolyte as described in claim 1, wherein, The compound represented by chemical formula 2 is at least one selected from compounds represented by chemical formulas 2A to 2C: [Chemical Formula 2A] N≡C-CH(CH3)2 [Chemical Formula 2B] N≡C-CH(CH2CH3)2 [Chemical formula 2C] N≡C-CH(CH3)CH2CH3.

7. The non-aqueous electrolyte as described in claim 1, wherein, The weight ratio of the first additive to the second additive is 10:90 to 30:

70.

8. The non-aqueous electrolyte as described in claim 1, wherein, Based on the total weight of the non-aqueous electrolyte, the total content of the additive is 10% to 20% by weight.

9. The non-aqueous electrolyte as described in claim 1, wherein, The non-aqueous electrolyte further includes at least one auxiliary additive selected from cyclic carbonates, halogenated carbonates, sulfonyl lactones, sulfates, phosphoric acids, borates, benzenes, amines, silanes, and lithium salts.

10. A lithium secondary battery comprising: a positive electrode, a negative electrode opposite to the positive electrode, a separator disposed between the negative electrode and the positive electrode, and the non-aqueous electrolyte as described in claim 1.

11. The lithium secondary battery as described in claim 10, wherein, The negative electrode contains silicon-based active materials.

Citation Information

Patent Citations

  • Penetration-resistant insert having improved penetration-resistance, protection panel for instep of a foot and safety shoes comprising the same

    KR1020240164626A

  • Soft x-ray optics with improved filtering

    KR1020250165692A